CFD analysis of phase change behaviour and frost growth under various conditions using mass transfer theory. (1st December 2022) - Wong, Joshua C.Q.; Pareek, Vishnu K.; Sun, Biao
Highlights: A dynamic multiphase CFD model is developed to study the frost formation process. Dimensionless numbers are used to calculate mass transfer rates. Parametric study on frosting rates and thickness growth was conducted. Two distinct high mass transfer rates are observed. Abstract: A frosting model based on mass transfer theory was developed using Computational Fluid Dynamics software to investigate frost growth on a horizontal surface. The mass transfer model utilizes dimensionless numbers to calculate the mass transfer coefficient to predict rate of frosting. The predicted frost thickness was generally within 20% of experimental data and was able to show the mass transfer behaviour for the frosting phenomenon. Compared to previous studies, water vapour condensation and frost growth in this study are governed by the 0 °C air temperature iso-surface which in turn is affected by the amount of frost developed as well as the operating conditions. The predictions by model show that mass transfer rates are higher at both the cold surface and the frost-air interface, which represents frost densification and thickness growth, respectively. A larger distinction between the two mass transfer rates is observed as the surface temperature becomes lower. Additionally, the effects of air humidity, velocity and temperature on frost formation at refrigeration conditions are investigated.